Acquisition of Water Solubility Diagrams in Ternary Systems (AOT/Organic Solvent/Alcohol) and Extraction of α‐Lactalbumin Using Reverse Micellar Systems. Issue 4 (26th April 2017) - Gomes, Glêce Milene Santana; Bonomo, Renata Cristina Ferreira; Veloso, Cristiane Martins; da Silva, Luis Henrique Mendes; da Costa Ilhéu Fontan, Rafael; Gandolfi, Olga Reinert Ramos; Gonçalves, Gabriel Ramos Ferreira; Sampaio, Vanessa Santos
Abstract: In this study water solubility curves were constructed and calorimetric measurements obtained for reverse micellar systems consisting of an alcohol (isopropanol or butanol), surfactant (AOT) and organic solvent (isooctane or hexane). Also evaluated were the effects of alcohol and solvent type and surfactant concentration on the extraction of the α‐lactalbumin (α–la). From the obtained solubility diagrams for ternary systems, it was concluded that isooctane presented the highest water solubility capacity in the center of the micelle systems with hexane, since isooctane has greater molecular volume and greater effect of the surfactant aggregation number. With respect to the alcohols, it was observed that isopropanol and butanol act in the system as a co‐surfactant, since they prefer to adsorb at the water/solvent interface. It was also verified that butanol improved water solubility inside the reverse micellar due to its contribution to increase the critical packing parameter. The amount of α‐la extracted increased proportionally with the AOT concentration for systems with isooctane and hexane. However, for systems with the latter solvent, the concentration of extracted protein first increases and then decreases. The extraction power of reverse micellar systems with isooctane was influenced by the type of alcohol with butanol showing better results. For systems containing hexane there was no effect of the alcohol added to the system on extraction power of α‐lactalbumin.